Odpowiedzi

Najlepsza Odpowiedź!
2009-11-19T23:32:24+01:00
X+1/3 = x+√2/3-√2+2
(x+1)(√2+2) = 3(x+√2)
3x-√2x+2x+3-√2+2 = 3x+3√2
-√2x+2x = 3√2-3+√2-2
x(-√2+2) = 4√2-5 |÷(2-2√)
x = 4√2-5/(2-2√) × (2+2√)/(2+2√) - usuwamy niewymierność z mianownika
x = (4√2-5)(2+2√)/(2-2√)(2+2√)
x = (8√2+8-10-5√2)/(4-2)
x = (3√2-2)/2
x = ³/₂√2 - 1
2009-11-19T23:41:56+01:00
Jesli x+1/3=x+√2/3-√2+2, to x jest rowne:
a. 2+√2
b. -2(√2+1)
c. -2√2-2

x+1/3=x+√2/3-√2 + 2 /3
x+1=3x+3√2/3-√2+6
x=3x+3√2/3-√2+5
x-5=3x+3√2/3-√2
( x+5)(3-√2 )=3x+3√2
3x-x√2 +15-5√2=3x+3√2
-x√2 +15-5√2=3√2
-x√2=8√2-15
-x=8-15√2/2
x=15√2/2-8
żadna z powyższych
2009-11-20T00:37:58+01:00
X+1/3=x+√2/3-√2+2 mnożymi stonami przez 3
3x +1 = 3x +√2 -3√2 + 6
3x +1 = 3x -2√2 +6
3x - 3x = -2√2 +6 -12
0 = -2√2 -6
sprzeczne